In situ single asperity wear at the nanometre scale. (17th February 2017) - Liao, Y.; Marks, L.
Abstract : The interface of two contacting materials experiences complex physical and possibly chemical reactions when one slides with respect to another. While tribology, a subject studying sliding contact, has been comprehensively elucidated for a variety of materials ranging from metals, carbides, inorganic materials and polymers, direct imaging data of the processes taken place at the nanometre or atomic scale have been greatly lacking. Recent proliferation of precise manipulation of a scanning nano-probe has provided a great tool to image sliding of single asperities, and single asperity nanotribology has been a rapidly developing area which provides model systems to investigate the fundamentals of sliding contacts and surface science. By implementing a nanoprobe in a higher resolution transmission electron microscope or a scanning electron microscope, the materials deformation of sliding single asperities have been revealed in real time, leading to insightful understandings of wear and friction. This article reviews recent reports on in situ transmission electron microscopy tribological investigations with an emphasis on materials degradation in mechanical and tribochemical reactions at the nanometre scale and at the surface.